Pancasila Perspective on the Development of Legal Philosophy: Relation of Justice and Progressive Law - Wawan Andriawan (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2022)
The development of philosophical science spreads to aspects of the operation of law along with the dynamics of human civilization. However, this philosophical concept must be filtered with the essential values, including Indonesia. This is because the fusion of philosophical ideas with elements as stated in the state constitution of a nation must be interpreted and crystallized in various legal products issued by a government. This study aims to describe the Pancasila perspective on the development of legal philosophy in Indonesia and analyze the meaning of 'justice' from a progressive legal perspective. This research is legal research using a conceptual approach and legislation. The legal materials used in this research are primary legal materials and secondary legal materials. These two materials are considered to examine the legal issues raised in this research. The result of this study is that the philosophy of law in Indonesia is based on the precepts of all the principles in Pancasila. Pancasila is actually in line with the flow of legal philosophy, namely Sociological Jurisprudence. This departs from the three dimensions of Pancasila, which is oriented to give birth to harmony from the implementation of rights and obligations in every existing legal subject. Then, the concept of progressive law provides the view that Justice is more oriented as substantive Justice, not procedural Justice. This is because Justice is the essence of the law itself; so that Justice cannot be calculated mathematically, cannot be interpreted purely textually, or can only be said to be 'fair' when there are two people who have the same share as others.